On-farm feed uniformity survey - Stark, C.R.; Hansen, J.A.; Goodband, Robert D.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
An on-farm feed manufacturing survey was conducted in conjunction with a mixer uniformity analysis. The survey collected information on producer size and type of operation, mixer type, manufacturing practices, and feed production. The survey represents 43 participants from across the U.S. Results indicate that 42% of the participants had mixer uniformity coefficients of variation of less than 10%, 47% were between 10-20%. and 11 % had CV's greater than 20%.
Keywords: Swine; On-farm feed manufacturing; Feed uniformity; Mixers